Developing a novel approach for passive damped LCL filter and controller parameter design using PSO algorithm in VSC-based islanded microgrids - Yared Bekele Beyene; Getachew Biru Worku; Lina Bertling Tjernberg (Array)
In this research, a new approach called Particle Swarm Optimization–Proportional–Integral (PSO-PI) is proposed for optimizing the gains of current and voltage controllers as well as the LCL filter parameters in voltage source converter (VSC)-based islanded microgrids. The control problem is framed as an optimization task, where PSO optimally tunes parameters. Unlike conventional offline methods, this study employs a simulation-based online optimization framework, integrating PSO within SIMULINK environment for dynamic, iterative adjustments, enhancing adaptability and efficiency. Well-founded mathematical models define parameter bounds, ensuring a unity ratio between converter-side and coupling inductances, and setting the switching-to-resonance frequency ratio by considering converter-side and output ripple currents. The objective function is formulated to improve the tracking performance of the outer voltage and inner current control loops with respect to their reference signals while minimizing total harmonic distortion (THD) and maintaining an optimal balance between filtering effectiveness and system performance. The PSO-PI approach achieves a more compact LCL filter while complying with IEEE-519 standards and outperforms the conventional method (CM). Simulations validate its effectiveness under various disturbances, including load changes, faults, and parameter variations, demonstrating improved damping and robustness in VSC-based islanded microgrids. Notably, improved transient response is achieved, with a 61.80% reduction in settling time and a 51.34% decrease in overshoot. Integrating PSO within the SIMULINK framework enables dynamic fine-tuning of VSC parameters through simulation-driven optimization, highlighting its potential as a robust microgrid control strategy.